The Effect of Liquid Organic Fertilizer and Urea Fertilizer on the Growth and Production of Kailan (Brassica oleracea) - Ondo Hanatha Tondang; Roida Ervina Sinaga; Chaula Lutfia Saragih (Indonesian Journal of Agriculture and Environmental Analytics, 2026)
The objective of this study was to determine how the use of liquid organic fertilizer and urea affects the yield of kailan. This study employed a randomized block design with 288 samples. After completing the planting process from the beginning to the end of the harvest period, the data collected through the studied parameters will be analyzed using SPSS ANOVA. The results show that all plant parameters, including height, number of leaves, stem diameter, and fresh weight, developed well and showed significant growth. The results of this study indicate that the use of liquid organic fertilizer and urea significantly affects the growth and yield of kailan.